Not starring Zadie Louise - McCullough, Joy (2022)
With her mom's job and theater on the line, Zadie is determined to help make their show Spinderella the hit of the season--that is unless she accidentally turns it into a disaster.
Ages 8 and Up.
Keywords: Theater -- Fiction